Biological synthesis of silver nanoparticles using animal blood, their preventive efficiency of bacterial species, and ecotoxicity in common carp fish. Issue 8 (11th March 2021) - Kakakhel, Mian Adnan; Wu, Fasi; Feng, Huyuan; Hassan, Zubair; Ali, Ihsan; Saif, Irfan; Zaheer Ud Din, Syed; Wang, Wanfu
Abstract: Possible high biodeterioration of the microorganisms due to their metabolic pathway and activities on stone materials causes solemn problems in cultural heritage. Different kinds of laboratory‐scale methods have been used for the reduction of microbial growth, that is, chemical, mechanical, and physical, which are cost‐effective and not ecofriendly. In the current study, an ecofriendly approach utilizing silver nanoparticles were synthesized using sheep blood serum. Transmission electron microscopy results have confirmed the spherical and well dispersed silver nanoparticles with an average size of 32.49 nm, while energy dispersive X‐ray has shown the abundance of silver nanoparticles. The efficiency against bacterial species was verified through laboratory‐scale testing. The strong antibacterial activity was confirmed when B‐AgNPs was tested against different bacterial species isolated from the Beishiku Cave Temple. The largest zone of inhibition was measured 26.48 ± 0.14 mm against Sphingomonas sp. while the smallest zone of inhibition measured was 9.70 ± 0.27 mm against Massilia sp. Moreover, these ecofriendly B‐AgNPs were tested for daily based dose in different concentrations (0.03, 0.06, and 0.09 mg/L) against common carp fish for a long exposure (20 days) and 6.5% fatality was found. The highest lethal concentration (LC50 ) for fish (0.61 ± 0.09 mg/L). No doubt, the laboratory scale applications have revealed the best results with minute toxicity in fish. Therefore, sheep serum should be continued to synthesize silver nanoparticles on a large scale. A strict monitoring system should be developed for the synthesis and application of AgNPs. Highlights: Animal blood contained a large number of proteins contents Proteins are macromolecules act as reductive agents Novel biological synthesis of Silver Nanoparticles using animal blood serum Investigation of biological activity using B‐AgNPs UV–VIS and XRD confirmed the nanoparticles synthesis TEM and EDX confirmed the well disperse nanoparticles Blood induced AgNPs are eco‐friendly